Thermodynamic Behaviour of Hydrates Drilling Muds - Lal, B. (Springer Nature, 2022)
The thermodynamic data for almost all the drilling mud tested for mitigating hydrate formation are reviewed in this section. The data provided in this section provides fundamental information on the effect of drilling mud additives on the hydrate phase equilibrium boundary data of drilling gas systems. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.